2006
DOI: 10.1111/j.1600-0420.2006.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual field defects in prematurely born patients with white matter damage of immaturity: a multiple‐case study

Abstract: ABSTRACT.Purpose: White matter damage of immaturity may affect visual, motor and cognitive functions. This multiple-case study presents standardized perimetry results in six teenagers and young adults born prematurely with visual dysfunction due to white matter damage of immaturity of pre-or perinatal origin. Methods: Six subjects, aged 13-25 years, born at a gestational age of 28-34 weeks, with white matter damage of immaturity documented by MRI, and optic disc appearances documented by fundus photography, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 14 publications
(18 reference statements)
4
35
0
Order By: Relevance
“…1,2 These include hyperopic refractive error, 3 optic disk cupping, 4 lower visual field impairment, 5 reduced central visual function, 3 and ocular motility deficits including nystagmus, strabismus, and supra-nuclear disorders of gaze. 3 Children born prematurely may exhibit subtle features of cognitive visual dysfunction, which may in part be related to periventricular white matter damage.…”
mentioning
confidence: 99%
“…1,2 These include hyperopic refractive error, 3 optic disk cupping, 4 lower visual field impairment, 5 reduced central visual function, 3 and ocular motility deficits including nystagmus, strabismus, and supra-nuclear disorders of gaze. 3 Children born prematurely may exhibit subtle features of cognitive visual dysfunction, which may in part be related to periventricular white matter damage.…”
mentioning
confidence: 99%
“…They also provide valuable information in different neurological and developmental disorders in children and young adults (Larsson et al 2004;Martin et al 2004;Jacobson et al 2006;Martin & Lundvall Nilsson 2007). However, although ADHD is a disorder that affects both the structure and function of the brain, there are, to our knowledge, no published papers describing VFs in children and adolescents with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…351 Selective dorsal stream dysfunction correlates with the finding that PVL shows a predilection for involving the lower visual fields. 141,142,283 These findings could be explained by bilateral injury to the superior striate or extrastriate cortex. Galetta and Grossman found that horizontal meridian corresponds to the base of the calcarine fissures, 186 which lie adjacent to the lesions of PVL.…”
Section: Dorsal and Ventral Stream Dysfunctionmentioning
confidence: 88%